Triples Activity Learning Model in Teaching Arabic for Graduate Students of Islamic Religious Education - Dhiauddin Dhiauddin; Nazaruddin Nazaruddin (Ta'dib, 2025)
The mastery of Arabic is an essential requirement for students in the Islamic Education Master Program at the Islamic University of Aceh, given its significant role in studying Islamic sciences. Despite its importance, Arabic learning within the program tends to be passive, limiting students' ability to acquire deeper and more applicable language skills. This study aims to analyze the implementation of Arabic language learning using the Triples Activity Learning approach, which is designed to enhance students' competence in Arabic interactively and effectively. This research employs a qualitative method with a case study approach. The subjects of the study are students enrolled in the Islamic Education Master Program. Data collection techniques include observations, interviews, and document analysis, ensuring comprehensive insights into learning practices. The collected data are analyzed through thematic analysis, and triangulation is applied as a strategy to maintain the validity and reliability of the findings.The study found that Arabic language learning plays a crucial role in understanding Islamic teachings and fostering global academic communication. The implementation of the Triples Activity Learning model, incorporating multimedia-based interactive methods, significantly enhances students' Arabic proficiency. The integration of three types of materialÔÇöscript study, hiw─ürat (dialogue), and istim─ü' (listening)ÔÇöproves effective in improving students' listening, reading, and speaking skills. Based on these findings, it is recommended that Arabic learning in higher education institutions adopts modern, adaptive, and interactive approaches to optimize language mastery.